Dynamic Modeling of Catfish Farming Development Using iThink Software - Febrian, Muhamad Zidane; Saka, Bima Ariya; Werdaya, Rangga Kusumah Putra Marsha; Tosida, Eneng Tita; Subandi, Kotim; Sugara, Victor Ilyas (Operations Research: International Conference Series, 2025)
This study analyzes the development of catfish farming in the Special Region of Yogyakarta (DIY) using a dynamic systems approach with iThink software. The model evaluates the relationships between local production, demand, external supply, and market prices over a 10-year period. The results indicate that local production can only partially meet demand, leading to a high dependency on external supply, primarily from Boyolali Regency and East Java. Simulations identify optimal strategies to enhance production efficiency, maximize land utilization, and reduce reliance on external supply. Model validation demonstrates that the simulation results align with historical data, making it a reliable tool for supporting sustainable strategic policy planning. This study is expected to provide solutions for food security and strengthen the self-sufficiency of the fisheries sector in DIY.